Political and psychological characteristics of individuals supporting various scenarios for increasing trust in government during wartime - KLYMENKO, Iryna; PYLYPENKO, Oleksandra (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . It was emphasized that due to the fact that in 2024 the planned change of power in Ukraine due to martial law will not take place, trust in the government will be the main source of ensuring its legitimacy. The study of the dynamics and structure of political trust, as well as the characteristics of people who are supporters of various scenarios of increasing the level of trust in the authorities, is an issue that is relevant not only of the theoretical side, but also from the position of ensuring a timely response to public requests to ensure the stability and support of the internal potential for the country's fight against the enemy.M e t h o d s . The methods of online survey of respondents using questionnaires and a panel of psychological methods were used to study the level of political participation, values, cognitive orientation (locus of control), and the level of paternalism in relation to government institutions.Content analysis was used to analyse the political discourse in social networks regarding the conditions for increasing trust in the authorities in wartime conditions. The scales selected on its basis were offered for evaluation by our subjects.R e s u l t s . Three groups of respondents with different levels of trust in the authorities were distinguished: complete distrust, partial distrust and unconditional trust. The political and psychological features of people with different levels of trust in the authorities were analysed, in particular differences in the level of political participation, orientation of the locus of control, political preferences of groups with partial and unconditional support of the authorities were revealed. The conditions put forward in the discourse on social networks as significant for maintaining / increasing trust in the current government were analyzed, as well as the analysis of differences in the importance of certain conditions in our subjects with different characteristics.C o n c l u s i o n s . A decrease in the level of trust in the authorities in the conditions of the prolongation of the war is demonstrated, a significant list of complaints against the actions of the current government is highlighted (increasing tendency to authoritarianism, lack of transparency in communication, insufficient actions to fight corruption, transfer of the economy to military rails, etc.) and a corresponding list of conditions that put forward various groups in order to return / increase trust in the authorities.
Keywords: political trust; institutional trust; social trust; war; power